Utilization of traditional bone-setters in the treatment of bone fracture in Ibadan North Local Government (2013)
The World Health Organization had recommended the integration of traditional and modern medicine. However traditional medicine as well as traditional bone-setting had received poor recognition in Nigeria. This notwithstanding traditional bone-setters still enjoys patronage from the populace in Ibadan and the practitioners abound in almost every part of the country. This study focused on the causes of fracture and utilization of traditional bone setters in Ibadan under the explanation of the functionalism and modernization theories. The study adopted the quantitative and qualitative method, with the survey of eighty-eight (88) patients and In-depth interview administered to eight (8) traditional bone setters and (4) patients. Majority (69.5 percent) of the respondents fall within the age range of 18-47 years. Findings revealed that there were more (55.7%) male patients than female (44.3%). A huge majority (85.7 percent) reported by that the major causes of fractures of the respondents was road traffic accidents, especially through the motor-cycle, while friends had major influence in the selection of traditional bone setting as a form of treatment among the patients. All the patients responded that they are willing to recommend the traditional bone-setter who treated them to others. Traditional bonesetters are well patronized and found to be relevant in the treatment of fractures in especially in Ibadan and in other communities in Nigeria. The study recommends maximum support and funding from governments in the training and establishment of traditional bone-setters in Nigeria. Integration of traditional medicines as well as traditional bone-setting with modern medicine should be encouraged in Nigeria.